2019
DOI: 10.1111/jopy.12499
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up or top‐down? Examining global and domain‐specific evaluations of how one's life is unfolding over time

Abstract: Objective We employed bottom‐up and top‐down perspectives to evaluate the link between how individuals view their lives as unfolding over time overall and in multiple life domains. Method Participants from an American adult lifespan sample (n = 1,003, mean age = 54.39 years, 49% female, 94% Caucasian) evaluated their recollected past, current, and anticipated future satisfaction in seven life domains (health, work, finances, contribution to others, relationships with one's children, close relationships, sex li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 89 publications
6
21
0
Order By: Relevance
“…Taking into account the contribution of the three domains to overall life satisfaction, the high strength correlation between satisfaction with family life and overall life satisfaction in both members of the couple is consistent with previous studies concluding that satisfaction in the family domain is a stronger contributor to overall life satisfaction than satisfaction in the job [ 8 , 19 , 42 ] and food [ 20 , 21 ] domains. The strong association between satisfaction with family life and overall life satisfaction is also in line with studies reporting that satisfaction with close relationships, such as a spouse, and relationships with one’s children made a greater contribution to overall life satisfaction than satisfaction in the job domain [ 4 ]. Nevertheless, it is worth noting that satisfaction with family life was the main contributor to life satisfaction for both members of the couple.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Taking into account the contribution of the three domains to overall life satisfaction, the high strength correlation between satisfaction with family life and overall life satisfaction in both members of the couple is consistent with previous studies concluding that satisfaction in the family domain is a stronger contributor to overall life satisfaction than satisfaction in the job [ 8 , 19 , 42 ] and food [ 20 , 21 ] domains. The strong association between satisfaction with family life and overall life satisfaction is also in line with studies reporting that satisfaction with close relationships, such as a spouse, and relationships with one’s children made a greater contribution to overall life satisfaction than satisfaction in the job domain [ 4 ]. Nevertheless, it is worth noting that satisfaction with family life was the main contributor to life satisfaction for both members of the couple.…”
Section: Discussionsupporting
confidence: 77%
“…The life satisfaction bottom-up theoretical approach suggests that an individual’s overall life satisfaction is informed by their satisfaction in diverse life domains [ 2 , 3 ]. Different studies have adopted this approach to assess the influence of different life domains (e.g., work, family, health, financial situation) on overall life satisfaction at an individual level in adult samples [ 4 , 5 , 6 , 7 , 8 ]. These findings have shown that evaluations of various life domains can make independent contributions to (i.e., predict) life satisfaction [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations